Efeito do cimento endodôntico e da técnica restauradora no comportamento em fadiga de dentes tratados endodonticamente: estudo in vitro - Vargas, Andressa Weber (2024)
This study aimed to evaluate the fatigue behavior of root canal treated teeth, filled with AH Plus Jet (AHP) or AH Plus Bioceramic Sealer (AHPB) and rehabilitated with mesio-occlusaldistal (MOD) restorations (direct resin composite) or endocrowns (indirect resin composite). Seventy human upper premolars were prepared and randomly divided into five experimental groups: AHP-MOD, teeth filled with AHP and rehabilitated with MOD restorations; AHP-EC, teeth filled with AHP and rehabilitated with endocrowns; AHPB-MOD, teeth filled with AHPB and rehabilitated with MOD restorations; AHPB-EC, teeth filled with AHPB and rehabilitated with endocrowns; Control group (intact teeth). A monotonic tests (n=10) were previously performed to define the fatigue parameters. Next, the cyclic fatigue test (n=60) was extended with an initial load of 100 N for 5,000 cycles, then 200 N for 10,000 cycles and increasing by 50 N every 10,000 cycles until fracture occurred. Fracture analysis was performed using a stereomicroscope. Fatigue failure loads and the number of cycles to failure were analyzed by the Kaplan-Meier and Mantel-Cox (Log Rank) test. Survival rates were calculated for each “step” of the fatigue test. Fracture types were analyzed descriptively. Teeth treated with AHP and restored with endocrowns achieved better results in both load resistance and number of cycles, compared to the AHP-MOD group and teeth filled with AHPB regardless of the restoration used (p<0.05). However, there is no significant difference when these groups were compared to the control (p>0.05). Most failures (50%) were catastrophic (longitudinal fracture). In conclusion, root canal treated teeth filled with an epoxy resin-based sealer and restored with endocrown-type restorations presented a superior fatigue behavior compared to MOD directs restorations or teeth filled with a calcium silicate-based sealer, regardless of the type of coronal rehabilitation.